OXIDATIVE STRESS IN CHILDREN CHRONIC HEPATITIS - Alice N. Azoicai; Bogdan A. Stana (Amaltea Medical Publishing House, 2017)
Oxidative stress reduces the efficacy of the immune response effector mechanisms, making the cells more susceptible to apoptosis. In lymphoid cells, free radicals interfere with the response to antiviral treatment, causing resistance to therapy and favoring chronic infection. One of the factors responsible for oxidative stress in chronic infection with hepatitis B is the production of pro-inflammatory cytokines. On the other hand, studies show that C hepatitis virus can directly induce oxidative stress in hepatocytes. Chronic C hepatitis core gene expression was associated with elevated reactive oxygen species markers, decreased intracellular and/or mitochondrial glutation content and increased level of oxidized thioredoxin and lipid peroxidation products. Moreover, increased level of the malonyl-dialdehyde in serum of patients with hepatocarcinoma is suggesting that MDA can be a reliable marker of liver injury quantification. Reduction of the oxidative stress can be done using antioxidant medication (hepatoprotectives, ursodeoxycholic acid and vitamin A, C, E), this approach representing an important benefit for the patient.